ADAPTING MODELS IN METAMODELS COMPOSITION PROCESSES - Florez Fernandez, Hector Arturo (Revista Vínculos, 2013)
In Model Driven Engineering (MDE) approaches, metamodels can change after the creation of conformant models. Moreover, changes applied on one metamodel can be result of a composition process. When metamodels change, model conformity can be broken. Once the conformity is broken, the model is unuseful and it is not possible to regain the conformity with the composite metamodel. This paper presents a proposal to solve models adaptation through a Domain Speci c Language (DSL). This DSL is used by metamodelers who are the people that know the domains abstracted by several metamodels, and know how to combine those meta-models in order to generate the composite metamodel. In addition, the DSL allows metamodelers to include the solu-tion for conformant models adaptation.